The Factors of Efficiency of Social-Economic Management of Higher Education - Sargsyan, Hasmik (Տիգրան Մեծ)
The sphere of education is in the center of attention of modern scientific research and political observations. The list of developed countries of the world has always been leading countries that are able to create a highly efficient and up-to-date and a flexible educational system. Practically all countries, which show a rapid economic growth, the development of education is one of the priorities of the state policy. In the context of modern financial constraints, it is necessary to effectively use the existing financial potential. In this regard, one of the most important components of public administration is budget management directed to the development of the education sector. In this research are presented some issues of effective management of higher education system and is analyzed the international experience in this field. Also the peculiarities of Armenian Higher Education sector are given from the point of view of state policy.
Keywords: Sociology; Education